1996
DOI: 10.1093/oxfordjournals.humrep.a019080
|View full text |Cite
|
Sign up to set email alerts
|

Fertilization and early embryology: Influence of maternal age on meiotic spindle assembly oocytes from naturally cycling women

Abstract: To examine the effects of maternal ageing on the meiotic apparatus, we obtained oocytes from naturally cycling women in two age groups, including younger (aged 20-25 years) and older (aged 40-45 years) women. Using high-resolution confocal microscopy we obtained a detailed picture of the meiotic spindle and chromosome placement during various phases of meiosis. Our data revealed that the meiotic spindle in older women is frequently abnormal, both with regard to chromosome alignment and the microtubule matrix t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
292
1
16

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 535 publications
(331 citation statements)
references
References 0 publications
22
292
1
16
Order By: Relevance
“…Battaglia et al, using oocytes of normal volunteers, reported that the proportion of oocytes with abnormal spindles was significantly higher in older than in younger woman and abnormal spindles were associated with abnormal chromosome distribution (21). Our data support their results, since comparing the age of different groups of patients involved in this study we found correlation between age of patients and number of oocytes obtained and percentage of oocytes with detected spindles (spindle positive oocytes).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Battaglia et al, using oocytes of normal volunteers, reported that the proportion of oocytes with abnormal spindles was significantly higher in older than in younger woman and abnormal spindles were associated with abnormal chromosome distribution (21). Our data support their results, since comparing the age of different groups of patients involved in this study we found correlation between age of patients and number of oocytes obtained and percentage of oocytes with detected spindles (spindle positive oocytes).…”
Section: Discussionsupporting
confidence: 90%
“…Our results support the observations of others that the presence of a birefringent spindle in human oocytes could predict a higher fertilization rate and a greater probability of embryo development (11,12). Thus, spindle visualization (spindle-based selection of oocytes) can help differentiate oocytes, and the presence of spindle can serve as an early indicator of oocyte viability (11,16,21). However, the relative position of the spindle within the oocytes does not appear to influence the developmental potential of embryos (12).…”
Section: Discussionsupporting
confidence: 89%
“…Although several previous studies reported that the quality of oocytes is associated with maternal age [10,[28][29][30][31][32], prior to the present study there has not been any report indicating whether cryo-survival of oocytes is related to maternal age of the oocyte. Ultrastructural abnormalities have been found in correlation with increase in maternal reproductive age of mouse oocytes [24].…”
Section: Discussioncontrasting
confidence: 53%
“…Oocyte quality begins to decrease after age 30, and drops rapidly after age 35 [6,7]. In older women, the meiotic spindle is frequently abnormal [1], and aging-associated oocyte aneuploidy and meiotic spindle defects have been described in mice [12]. However, to date, there are few studies investigating the association between aging and oocyte function.…”
Section: Introductionmentioning
confidence: 99%